TATAKELOLA LANSKAP RAWAPENING BERDASARKAN TINGKAT RESIKO BENCANA LINGKUNGAN DI SUB DAS RAWAPENING (Landscape governance of Rawapening based on the level of environmental disaster risk in the Rawapening Sub Watershed) - Djati Mardiatno; faridah faridah; sunarno sunarno; Dwi Wahyu Arifudiin Najib; Yuli Widyaningsih; M. Anggri Setiawan (Jurnal Penelitian Pengelolaan Daerah Aliran Sungai (Journal of Watershed Management Research), 2021)
ABSTRACT Lake ecosystem balance is influenced by the interaction and interrelation of upstream and downstream processes of catchment. Environmental degradation upstream affects the trophic status of the lake, triggering the risk of environmental disasters. Integrated lake management is a form of governance to achieve sustainable development goals. This study aims to analyze the implementation of the Rawapening Lake management program plan spatially by considering the environmental risk conditions of the Rawapening catchment area. Semi-quantitative analysis is used to assess the level of disaster risk in Rawapening catchment area. The zoning results of environmental disaster risk areas are used as the basis for the implementation of the 2019 Rawapening lake management plan descriptively. The results showed that Rawapening catchment area has a very low, low, medium, high, and very high risk levels. Panjang Sub Watersheds, Galeh Sub Watersheds, Parat Sub Watersheds, Sraten Sub Watersheds have a high to very high risk level. The Rengas Sub Watershed, Torong Sub Watershed falls into the medium risk category. Low to very low risk levels are scattered in the Legi Sub Watershed, the Kedung Ringis Sub Watershed, and the Ringis Sub Watershed. The complexity of the problems in the agricultural, livestock, residential and industrial sectors is the main contributor to sediment and pollutants in the lake system. The integration of upstream and downstream processes is used as a consideration in conducting spatial planning for Rawapening Lake management to achieve management objectives. Keywords: environmental disaster; eutrophication; landscape management ABSTRAKKeseimbangan ekosistem danau dipengaruhi oleh interaksi dan interelasi proses hulu dengan hilir DAS. Degradasi lingkungan di bagian hulu berpengaruh terhadap status trofik danau, memicu resiko bencana lingkungan. Pengelolaan danau secara terpadu merupakanwujud tata kelola untuk mencapai tujuan pembangunan berkelanjutan. Penelitian ini bertujuan untuk menganalisis implementasi rencana program pengelolaan Danau Rawapening secara spasial dengan mempertimbangkan kondisi resiko bencana lingkunganSub DAS Rawapening. Analisis semi kuantitatif digunakan untuk menilai tingkat resikobencana Sub DAS Rawapening. Hasil zonasi kawasan resiko bencana lingkungan dijadikandasar dalam impelementasi Rencana Pengelolaan Danau Rawapening Tahun 2019 secaradeskriptif. Hasil penelitian menunjukkan Sub DAS Rawapening memiliki tingkat resiko sangatrendah, rendah, sedang, tinggi, dan sangat tinggi. Sub Sub DAS Panjang, Sub Sub DAS Galeh,Sub Sub DAS Parat, Sub Sub DAS Sraten memiliki tingkat resiko tinggi hingga sangat tinggi.Sub Sub DAS Rengas, Sub Sub DAS Torong masuk ke dalam kategori resiko sedang. Tingkatresiko rendah hingga sangat rendah tersebar pada Sub Sub DAS Legi, Sub Sub DAS KedungRingis, Sub Sub DAS Ringis. Kompleksitas permasalahan dalam sektor pertanian, peternakan,permukiman dan industri menjadi penyumbang utama sedimen dan polutan pada system danau. Integrasi proses hulu dengan hilir dijadikan sebagai pertimbangan dalam melakukan perencanaan spasial pengelolaan Danau Rawapening untuk mecapai tujuan pengelolaan.Kata kunci: bencana lingkungan; eutrofikasi; pengelolaan lanskap